A cell management system to support robotic assembly - Saiful Bahri, Mohamed; David, Petty; D.K., Harrison (2001)
There is an increasing requirement for the assembly of wider ranges of products in relatively small lot sizes. Consequently, robots are seen as being attractive as an assembly method. There has been much work on developing advanced robot grippers and applying vision systems/artificial intelligence. There has, however, been relatively little work on the overall problem of controlling robotic assembly cells (RACs) and their integration into the wider manufacturing organisation. This paper describes the design of a cell management system (CMS) based on a standard personal computer. The CMS supports RAC operations by managing/presenting data relevant to the cell operator. It also provides an interface between the cell and other organisational computer systems. Furthermore, the CMS allows error checking and recovery functionality to be implemented within an RAC without the need for modifications to the robot controller. Finally, the paper describes a pilot cell developed to test the CMS design.